2011
DOI: 10.1007/s10694-011-0228-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Air Velocity on the Detection of Fires in Conveyor Belt Haulageways

Abstract: A series of large-scale experiments were conducted in an above-ground fire gallery using three different types of fire-resistant conveyor belts and four air velocities for each belt. The goal of the experiments was to understand and quantify the effects of air velocity on the detection of fires in underground conveyor belt haulageways and to determine the rates of generation of toxic gases and smoke as a fire progresses through the stages of smoldering coal, flaming coal, and finally a flaming conveyor belt. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…More detailed information on the effect of air velocity obtained in this study can be found in Ref. 10.…”
Section: Fire Intensities Growth Rates and Co Productionmentioning
confidence: 99%
“…More detailed information on the effect of air velocity obtained in this study can be found in Ref. 10.…”
Section: Fire Intensities Growth Rates and Co Productionmentioning
confidence: 99%
“…The authors of the test results have jointly determined the flammability of rubber materials, which are common to conveyor tyres, conveyor belts and insulation of power cables, and have compared the thermal magnitude of the cargo quantities of these materials to other fuels that are publicly transported 27 , 28 . In turn, the smoke production of a material and the toxicity of the products of its thermal decomposition and combustion depend mainly on the chemical composition and combustion temperature of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…3 Owing to the underground tunnel environment, narrow spaces, and complicated ventilation network, serious secondary disasters can be caused by disasters combining with each other. [4][5][6][7] Jarosław Brodny revealed that numerical methods could be successfully used for analysing fire and ventilation phenomena in closed headings. 8,26 Aiming at the major safety demands for coal mines, many types of disaster smoke flow simulation software have developed by scholars to study the evolution laws and damage effects of smoke flow caused by fires.…”
Section: Introductionmentioning
confidence: 99%
“…The main factor for the heavy casualties is the spread of the smoke stream generated by the fire in the ventilation network 3 . Owing to the underground tunnel environment, narrow spaces, and complicated ventilation network, serious secondary disasters can be caused by disasters combining with each other 4‐7 . Jarosław Brodny revealed that numerical methods could be successfully used for analysing fire and ventilation phenomena in closed headings 8,26 .…”
Section: Introductionmentioning
confidence: 99%